Panorama de la littérature vepse - Gibert, Guillaume (Études finno-ougriennes, 2022)
The aim of this paper is to give a general overview of Vepsian literature. From a brief description of the oral literature and the development of the written language, we try to set out the broad lines of this literature through the two major genres: poetry, the most productive one, marked by Nikolai Abramov’s personality and poetic works; and prose, a more recent genre, coming mainly from translation but now expanding. Nikolai Abramov’s, Alevtina Andrejeva’s, Nina Zaiceva’s, Valentina Lebedeva’s, Mihail Bašnin’s and Igor Brodski’s works are illustrated by several excerpts and examples: translated in French, they show the original features of the Vepsian literature. Cet article se propose de dresser un panorama de la littérature vepse. À partir d’une brève présentation de la littérature orale et de la création de la langue écrite, nous tâchons d’exposer les grandes lignes de cette littérature à travers les deux genres majeurs qui la constituent : la poésie, genre le plus productif, marqué par la personnalité et l’œuvre majeure de Nikolai Abramov et la prose, genre plus jeune, issu essentiellement de la littérature de traduction et en voie de construction. Une présentation des œuvres de Nikolai Abramov, d’Alevtina Andrejeva, de Nina Zaiceva, de Valentina Lebedeva, de Mihail Bašnin, d’Igor Brodski, accompagnée d’exemples traduits, illustre ce parcours à travers cette littérature originale.